2017
DOI: 10.5812/ogcr.11440
|View full text |Cite
|
Sign up to set email alerts
|

Genital Warts (Anogenital warts)

Abstract: Anogenital warts (AGWs) are the most prevalent sexually transmitted viral infections in the United States of America. Symptomatic warts can be seen in nearly 1% of the population aged 15 to 49 years. Genital warts are highly contagious through sexual contact. AGWs can be diagnosed by careful visual inspection. Several methods have been described for the treatment of warts; however, all have their own limitations and are not always successful. Warts often recur even after being completely removed. The treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…There was an apparent complete intra-and perioral warts resolution using cimetidine. This is seen in HIVpositive adults that presented with recalcitrant mucosal warts that failed to respond to therapies like curettage and cautery, cryocautery, and oral etretinate [1]. Mitsuishi et al (2003) showed that higher oral dose (30-40 mg/kg/day) was more effective in treating multiple viral warts [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There was an apparent complete intra-and perioral warts resolution using cimetidine. This is seen in HIVpositive adults that presented with recalcitrant mucosal warts that failed to respond to therapies like curettage and cautery, cryocautery, and oral etretinate [1]. Mitsuishi et al (2003) showed that higher oral dose (30-40 mg/kg/day) was more effective in treating multiple viral warts [17].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, no definitive evidence suggests that one treatment is superior to another, and no single therapy is ideal for all patients or warts. Factors that affect response include the presence of immunosuppression and compliance, consisting of either a single or complete treatment course [1,2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 AGWs typically do not cause substantial morbidity or mortality, but the high rate of recurrence might interfere with the patient's quality of life. 12,13 When the HPV infection leads to penile cancer, the condition can be devastating, especially in advanced stages. 3 Various treatment modalities are available, but there is no clear evidence supporting the superiority of any one treatment over another.…”
Section: Introductionmentioning
confidence: 99%